Creatinin excretion during the period of twenty-four hours in children from five to eleven years old - Martins, Ignez Salas (1974)
It was studied the creatinine excretion over a period of twenty four hours in children from five to eleven years of age. During this period the creatinine excretion was constant and without circadian rhythm.